The Electrical Characteristics of Aluminium Doped Zinc Oxide Thin Film for Humidity Sensor Applications - N. D. Md Sin; M. Fuad Kamel; Rosalena Irma Alip; Zulfakri Mohamad; M. Rusop (Advances in Materials Science and Engineering)
The electrical characteristics of aluminum (Al) doped zinc oxide (ZnO) thin film for high sensitivity humidity sensors are presented. The effects of Al doping concentration at 0∼0.6 at % on the Al doped ZnO thin film properties were investigated using current-voltage measurement. The optical and structural properties were characterized using photoluminescence (PL), scanning emission microscope (SEM), and X-ray diffraction (XRD). Parameter 0.6 at % Aluminum doped show high sensitivity and suitable for humidity sensor. PL show an emissions band with two peaks centered at about 380 nm (ultra-violet (UV)) and 600 nm (green) in a room temperature. The length of the nanorods increases as the doping concentration increases. XRD results show the intensity of the (002) peak decreased with the increasing of doping concentration.